2020
DOI: 10.1111/iwj.13491
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of routine blood markers for predicting amputation/re‐amputation risk in diabetic foot

Abstract: Diabetic foot is challenging progressive disease which requires multisystemic control. Neuropathy, arteriopathy, and cellular responses should treated collaboratively. Despite all medical advances, diabetic foot can highly resulted with amputation and also re‐amputation can be required because of failed wound healing. In this study, we aimed to investigate the relation between blood parameters and amputation events. Diabetic 323 patients include to the study who referred to orthopaedic clinic for amputation. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
1
9
1
Order By: Relevance
“…2-2590 days were reported in the literature from the first operation to reoperation [17]. The general opinion is that these patients should be closely followed-up within the first six months [20].Although, various risk factors for reoperation (coronary artery disease, chronic kidney failure, low albumin levels, low lymphocyte count, anemia) were reported [13,16,17,21,22], we did not find a statistically significant relationship between the risk factors and re-operation in this study. This may be explained by the fact that the majority of our patients have already these risk factors.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…2-2590 days were reported in the literature from the first operation to reoperation [17]. The general opinion is that these patients should be closely followed-up within the first six months [20].Although, various risk factors for reoperation (coronary artery disease, chronic kidney failure, low albumin levels, low lymphocyte count, anemia) were reported [13,16,17,21,22], we did not find a statistically significant relationship between the risk factors and re-operation in this study. This may be explained by the fact that the majority of our patients have already these risk factors.…”
Section: Discussioncontrasting
confidence: 61%
“…Patients who should undergo amputation at the possible distal level to avoid the impairment of their quality of life and functionality. Many factors affect wound healing in patients after amputation surgery [14,[16][17][18][19]. The median period from the initial surgery to the second surgery was six weeks in our study.…”
Section: Discussionmentioning
confidence: 71%
“…In diabetic patients, amputations re-amputations represent frequent complication. Guelcu et al showed that CRP, together with lower albumin, higher HbA1c, and higher creatinine levels is associated with poor prognosis and re-amputation [ 38 ]. Diabetes induces dysregulation of miRNA expression that is associated with the development of macrovascular complications, including PAD [ 39 ] and dysregulates miRNAs expression related to atherosclerosis [ 40 ].…”
Section: Inflammation and Padmentioning
confidence: 99%
“…The number of such patients is rapidly increasing, as is the number of complications associated with the disease [ 5 , 6 , 7 , 8 , 9 ]. One of these complications, which permanently disables a person and is accompanied by the appearance of nonhealing or poorly healing ulcers on the distal parts of the lower extremities, is known in the medical literature as diabetic foot ulcers or diabetic foot syndrome (DFS) [ 10 , 11 , 12 , 13 ], which is the leading cause of non-traumatic lower extremity amputation [ 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%